2002
DOI: 10.1016/s0736-0266(01)00084-5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of basal TGFβ1 levels by EMF coincident with chondrogenesis – implications for skeletal repair and tissue engineering

Abstract: Members of the TGFP/BMP gene family regulate cartilage and bone development. These genes are re-expressed in bone repair and are thought to mediate chondro-and osteoprogenitor cell differentiation. These observations have led to a therapeutic strategy of introducing these growth factors into experimental cartilage and bone defects. Therapeutic efficacy, however, has been limited by diffusion or inactivation of these growth factors from the desired site and by the inability to deliver sustained concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…47 In vitro and in vivo studies showed that PEMF stimulation leads to an increase of transforming growth factor b, thereby improving bone development, reducing cartilage damage and increasing chondrocyte proliferation. 6,47,83,98 Clinical studies showed promising results for fracture nonunion and for recovery after arthroscopic treatment of focal cartilage knee lesions. 161,462 Therefore, PEMF stimulation may be effective for talar OCDs after arthroscopic treatment by producing effects that suppress inflammation, promote tissue healing, and relieve pain.…”
Section: Part II -Primary Arthroscopic Debridement and Bone Marrow Stmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In vitro and in vivo studies showed that PEMF stimulation leads to an increase of transforming growth factor b, thereby improving bone development, reducing cartilage damage and increasing chondrocyte proliferation. 6,47,83,98 Clinical studies showed promising results for fracture nonunion and for recovery after arthroscopic treatment of focal cartilage knee lesions. 161,462 Therefore, PEMF stimulation may be effective for talar OCDs after arthroscopic treatment by producing effects that suppress inflammation, promote tissue healing, and relieve pain.…”
Section: Part II -Primary Arthroscopic Debridement and Bone Marrow Stmentioning
confidence: 99%
“…436 In vitro and in vivo studies have shown that PEMFs act as adenosine A2a agonists, leading to an increase of transforming growth factor b-1, thereby improving bone development, reducing cartilage damage and increasing chondrocyte proliferation. 6 Clinically, its favorable eff ects are less obvious. PEMF as a solitary treatment for osteoarthritis of the knee has been repeatedly investigated, with confl icting results.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations on the mechanism of action of IC technology have been performed with the PEMF signal which is FDA approved for fracture healing but not spinal fusion [1,4,8,11,29,43,44,51,64]. There is only one study using the PEMF signal that is clinically approved for spinal fusions [61] and a few studies with CMF [11,20,21,58].…”
Section: Inductive Couplingmentioning
confidence: 99%
“…These in vitro studies have shown that chondrocyte proliferation and matrix synthesis are significantly enhanced by PEMF stimulation [8,9]. In vivo, it up-regulates the gene expression of growth factor TGF-β and prevents the catabolic effects of inflammatory cytokines [1,2,9].…”
Section: Discussionmentioning
confidence: 99%
“…This treatment has well documented physiological effects on cells and tissues such as the upregulation of gene expression of members of the TGF-β (transforming growth factor) super family [1,2]. It also enhances chondrogenic proliferation, differentiation and synthesis of cartilage extracellular matrix proteins [8,9].…”
Section: Introductionmentioning
confidence: 99%